2019
DOI: 10.1080/03007995.2019.1584505
|View full text |Cite
|
Sign up to set email alerts
|

A network meta-analysis of the efficacy and safety of baloxavir marboxil versus neuraminidase inhibitors for the treatment of influenza in otherwise healthy patients

Abstract: Objective: Baloxavir marboxil (baloxavir) is the first cap-dependent endonuclease inhibitor being studied for the treatment of influenza in single oral dosing regimen. This network meta-analysis (NMA) evaluated the efficacy and safety of baloxavir compared to other antivirals for influenza in otherwise healthy patients. Methods: A systematic literature review was performed on 14 November 2016 in Medline, Embase, CENTRAL, and ICHUSHI to identify randomized controlled trials assessing antivirals for influenza. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 36 publications
4
19
0
2
Order By: Relevance
“…These results are consistent with previous findings reported in the NMA on OwH patients conducted by Taieb et al showing that baloxavir was more effective than other antivirals regarding the reduction of viral titer within 24 hours. Interestingly in the OwH population, baloxavir was more effective than zanamivir in the alleviation of influenza symptoms, which was not confirmed among the HR population [15].…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…These results are consistent with previous findings reported in the NMA on OwH patients conducted by Taieb et al showing that baloxavir was more effective than other antivirals regarding the reduction of viral titer within 24 hours. Interestingly in the OwH population, baloxavir was more effective than zanamivir in the alleviation of influenza symptoms, which was not confirmed among the HR population [15].…”
Section: Discussionmentioning
confidence: 77%
“…The mean decline in virus titer from the baseline at 24h after treatment was significantly greater for baloxavir than for other drugs [15]. Baloxavir demonstrated a comparable safety profile to other antivirals, except for total drug-related adverse events (DRAE) where it demonstrated a decrease compared to oseltamivir and laninamivir [15].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In a recent clinical trial, oral BXM treatment resulted in a 3.5 log 10 TCID 50 /ml reduction in viral shedding at 24 hours post-treatment, whereas OST achieved only a 1.5 log 10 TCID 50 /ml reduction [6]. Previous reports have similarly demonstrated that baloxavir has a greater antiviral effect than OST: a network meta-analysis of past randomized controlled trial data showed that baloxavir-treatment was significantly more effective in reducing infectious viral tires at 24 hours after administration than OST, and other NAIs including zanamivir and peramivir [24].…”
Section: Plos Pathogensmentioning
confidence: 89%